Legal Aspects Around Satellite Constellations - Froehlich, Annette (Studies in Space Policy, 2019)
This book is based on an initiative made by the European Space Policy Institute, the European Centre for Space Law and the German Aerospace Center. Students and young professionals worlwide were invited to submit a paper on this topic analyzing and discussing relevant aspects on either environment, economy, security, licencing, or control. The best papers have been included in this volume.